2023
DOI: 10.1002/alz.13529
|View full text |Cite
|
Sign up to set email alerts
|

Retina pathology as a target for biomarkers for Alzheimer's disease: Current status, ophthalmopathological background, challenges, and future directions

Jessica Alber,
Femke Bouwman,
Jurre den Haan
et al.

Abstract: There is emerging evidence that amyloid beta protein (Aβ) and tau‐related lesions in the retina are associated with Alzheimer's disease (AD). Aβ and hyperphosphorylated (p)‐tau deposits have been described in the retina and were associated with small amyloid spots visualized by in vivo imaging techniques as well as degeneration of the retina. These changes correlate with brain amyloid deposition as determined by histological quantification, positron emission tomography (PET) or clinical diagnosis of AD. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 117 publications
0
7
0
Order By: Relevance
“…Moreover, a wide range of retinal microvascular and choriocapillaris changes in AD patients such as lower densities, sparser vasculature, increased tortuosity, and lower fractal dimensions have been shown in OCTA studies. 8 , 49 , 50 , 51 , 52 , 53 Here we showed that EOAD patients had lower retinal microvascular and choriocapillaris densities and sparser retinal microvascular and choriocapillaris compared to controls. These findings are in line with previous OCTA analyses.…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, a wide range of retinal microvascular and choriocapillaris changes in AD patients such as lower densities, sparser vasculature, increased tortuosity, and lower fractal dimensions have been shown in OCTA studies. 8 , 49 , 50 , 51 , 52 , 53 Here we showed that EOAD patients had lower retinal microvascular and choriocapillaris densities and sparser retinal microvascular and choriocapillaris compared to controls. These findings are in line with previous OCTA analyses.…”
Section: Discussionmentioning
confidence: 52%
“…Because of the lack of standardised protocols for in vivo retinal OCT analysis in murine models of AD, analysis has recently been attempted in humans [ 85 ]; it would be necessary to determine certain recommendations for the use of retinal imaging as a potential biomarker of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…This, coupled with the development of advanced non-invasive imaging technologies that can monitor retinal structure and function, makes the retina a powerful platform to interrogate neurodegenerative diseases. Indeed, retinal imaging and histopathological studies have identified changes in the retinal ganglion cell layer, retinal vasculature, and the optic nerve in patients with mild cognitive impairment and early-stage Alzheimer’s disease 5761 . In this study, using semi-automated OCT segmentation, we observed thinning of the photoreceptor outer nuclear layer and thickening of the outer plexiform layer in GRN mutation carriers compared to healthy controls, likely indicative of photoreceptor loss and microglial expansion.…”
Section: Discussionmentioning
confidence: 99%